Poverty and employment in Peru: the contributions of the National Living Standards Surveys (ENNIV) 1985-1994 - Yamada, Gustavo (1995)
The author analyzes tire contributions of the four National Living Standards Surveys (ENNIV) to the political, economic and social policy research and design in Peru over the last decade. He also lists the principal lines to be pursued in tracking living standards in the future based on these surveys and on the assumption that there will now be a greater availability of material and human resources for this purpose.